Lasers and energy devices for the skin - Goldman, Mitchel P. (CRC Press, 2013)
Technical developments have continued with the various uses for different types of laser device - particularly with fractionated lasers, laser liposuction, and the treatment of cellulite. The edition has been revised to ensure the reader has a guide to the refinements, but can also easily locate the practical treatment parameters for each device.